2013
DOI: 10.1155/2013/852195
|View full text |Cite
|
Sign up to set email alerts
|

Role ofCampylobacter jejuniInfection in the Pathogenesis of Guillain-Barré Syndrome: An Update

Abstract: Our current knowledge on Campylobacter jejuni infections in humans has progressively increased over the past few decades. Infection with C. jejuni is the most common cause of bacterial gastroenteritis, sometimes surpassing other infections due to Salmonella, Shigella, and Escherichia coli. Most infections are acquired due to consumption of raw or undercooked poultry, unpasteurized milk, and contaminated water. After developing the diagnostic methods to detect C. jejuni, the possibility to identify the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
136
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 120 publications
(177 reference statements)
0
136
1
4
Order By: Relevance
“…With polio almost eradicated globally, GBS has now become the most common cause of acute flaccid paralysis (AFP) with an annual incidence of 0.6-4.0 cases per 100000 population [4,5]. Campylobacter spp., particularly Campylobacter jejuni, have been described as one of the leading causes of human gastroenteritis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With polio almost eradicated globally, GBS has now become the most common cause of acute flaccid paralysis (AFP) with an annual incidence of 0.6-4.0 cases per 100000 population [4,5]. Campylobacter spp., particularly Campylobacter jejuni, have been described as one of the leading causes of human gastroenteritis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…With polio almost eradicated globally, GBS has now become the most common cause of acute flaccid paralysis (AFP) with an annual incidence of 0.6-4.0 cases per 100000 population [4,5]. Campylobacter spp., particularly Campylobacter jejuni, have been described as one of the leading causes of human gastroenteritis [1][2][3][4][5]. Pathogenic features of C. jejuni influencing the development of GBS have been described, with C. jejuni infections reportedly constituting the majority of GBS cases [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the GBS is associated with various types of infection (such as Campylobacter jejuni , Cytomegalovirus, Epstein‐Barr virus, Mycoplasma pneumoniae , and hepatitis E virus) which lead to a cross‐reaction with nervous system, demyelination of neurons, and finally initiation of nervous signs and symptoms by stimulating immune system (van Doorn & Jacobs, 2016; Taheraghdam et al., 2014). Simultaneously, accumulating evidence has indicated that the antecedent infection with C. jejuni enteritis may trigger the generation of AGA (Nyati & Nyati, 2013). Moreover, previous studies have shown that Cytomegalovirus (CMV), a member of the β herpes family may lead to the incidence of GBS and is second only to C. jejuni enteritis (Orlikowski et al., 2011; Taheraghdam et al., 2014).…”
Section: Introductionmentioning
confidence: 99%